Peran Guru Ppkn Dalam Menanamkan Kesadaran Moral Siswa Kelas VII di SMP Swasta Imelda Medan - Astina maya Nainggolan; Lukman Pardede; Monalisa Siahaan; Dewi Lestari Pardede (International Forum of Researchers and Lecturers, 2023)
This research aims to: Find out the role of PPKn teachers in instilling moral awareness in students at the Imelda Medan Private Middle School. Researchers used qualitative descriptive methods. This research data is the basis and main capital for forming students' character and strengthening national identity, namely the cultivation of morals in education. The role of civic education teachers in instilling students' moral awareness is to provide learning motivation for students. The three moral components are knowledge, feelings and actions. The data collection techniques in this research are observation, interviews, and documentation. The researcher concluded that the solution to the problems faced by teachers in fostering students' moral awareness is by teachers becoming good individuals so that students can emulate them.